1999
DOI: 10.1093/carcin/20.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits cyclooxygenase-2 transcription in bile acid- and phorbol ester-treated human gastrointestinal epithelial cells

Abstract: We investigated whether curcumin, a chemopreventive agent, inhibited chenodeoxycholate (CD)- or phorbol ester (PMA)-mediated induction of cyclooxygenase-2 (COX-2) in several gastrointestinal cell lines (SK-GT-4, SCC450, IEC-18 and HCA-7). Treatment with curcumin suppressed CD- and PMA-mediated induction of COX-2 protein and synthesis of prostaglandin E2. Curcumin also suppressed the induction of COX-2 mRNA by CD and PMA. Nuclear run-offs revealed increased rates of COX-2 transcription after treatment with CD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(155 citation statements)
references
References 38 publications
10
141
0
4
Order By: Relevance
“…Accumulating evidences suggest that curcumin inhibits the expression of COX-2 in several experimental models (Zhang et al, 1999;Chun et al, 2003;Surh, 2003;Kang et al, 2004). Consistent with these, through the present study, we have demonstrated that curcumin also effectively inhibits the expressions of COX-2 mRNA and protein induced by UVB irradiation in a human keratinocyte cell line HaCaT, which seems to be, to our knowledge, the first report.…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidences suggest that curcumin inhibits the expression of COX-2 in several experimental models (Zhang et al, 1999;Chun et al, 2003;Surh, 2003;Kang et al, 2004). Consistent with these, through the present study, we have demonstrated that curcumin also effectively inhibits the expressions of COX-2 mRNA and protein induced by UVB irradiation in a human keratinocyte cell line HaCaT, which seems to be, to our knowledge, the first report.…”
Section: Discussionsupporting
confidence: 91%
“…Cells were then treated with fresh 3% fetal bovine serum RPMI with or without LPS (50 ng/ml). Nuclear extracts were obtained 30 min later as described previously (23). Briefly, cells were lysed by incubation in buffer A (10 mM HEPES, pH 7.9, 1.5 mM MgCl 2 , 10 mM KCl, 0.5 mM dithiothreitol, and 0.2 mM phenylmethylsulfonyl fluoride) on ice for 15 min, followed by vortexing for 10 s. Nuclei were pelleted, and nuclear extracts were obtained by high salt extraction after incubating nuclei in buffer C (20 mM HEPES, pH 7.9, 25% glycerol, 420 mM NaCl, 1.5 mM MgCl 2 , 0.2 mM EDTA, 0.5 mM dithiothreitol, and 0.2 mM phenylmethylsulfonyl fluoride) for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…At least part of the effect of curcumin on inducible PGE 2 production in human blood can be attributed to inhibition of COX2 transcription, which might be due to the inhibition of the NF-B-activating enzymes IKK-␣/␤. 57,58 The effect of curcumin described in an ex vivo assay developed using blood from healthy volunteers 56 was associated with a daily oral dose which furnished plasma levels in the 10 −8 M range in patients with advanced colorectal cancer. 16 This concentration of curcumin is less than a hundredth of that shown in vitro to elicit an effect in blood or colon cells.…”
Section: Dose-effect Relationshipsmentioning
confidence: 99%